1979
DOI: 10.1159/000260410
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Changes and Dental Caries in 7-Year-Old Children Given Fluoride Tablets from Shortly after Birth

Abstract: In 1969, a caries preventive program was initiated in a part of Denmark where parents of infants were offered prescriptions for fluoride tablets for daily use. When requested new prescriptions were supplied free of charge by the County Dental Officer. In 1976, samples of children about 7 years of age who had received a total of 0, 1–800, 800–1,600 and more than 1,600 0.25 mg F tablets were examined. A positive association between number of tablets prescribed and dental fluorosis was found in erupted permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…For instance, a number of studies found a positive association between the use of fluoride tablets and the prevalence of dental fluorosis in erupted permanent teeth [Thylstrup et al, 1979;Kalsbeek et al, 1992]. A meta-analysis [Ismail and Bandekar, 1999] showed that administering fluoride supplements increased the risk of dental fluorosis by a factor of at least 2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a number of studies found a positive association between the use of fluoride tablets and the prevalence of dental fluorosis in erupted permanent teeth [Thylstrup et al, 1979;Kalsbeek et al, 1992]. A meta-analysis [Ismail and Bandekar, 1999] showed that administering fluoride supplements increased the risk of dental fluorosis by a factor of at least 2.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may help in an under standing of the often reported lower fre quency of nonfluoride opacities noted in op timally fluoridated areas [Richards et al, 1967;Thylstrup et al, 1979]. The various forms of enamel opacities of different etiol ogy have nevertheless been considered to gether in several studies as a single entity, 'mottling' [for review see Small and Mur ray, 1978], This approach based on objec tive clinical criteria gives useful information relative to the cosmetic effect of water borne fluoride, though less information can be derived from such studies concerning an individual's exposure to fluoride during the period of tooth formation.…”
mentioning
confidence: 92%
“…He came to the conclusion that fluoride supplements are not particularly effective because of compliance problems. It should also be taken into account that fluoride supplementation increases the risk of fluorosis [Thylstrup et al, 1979;Riordan, 1993Riordan, , 1999.…”
mentioning
confidence: 99%